PENGARUH KEJELASAN SASARAN ANGGARAN DAN PENGENDALIAN AKUNTANSI TERHADAP AKUNTABILITAS KINERJA DI SEKRETARIAT DAERAH (SETDA) KAB. LEBAK - Amara Austin; Ela Widasari; Imas Fatimah (Universitas La Tansa Mashiro, 2023)
The Regional Secretariat (SETDA) is an auxiliary element of the local government is a public organization. This study aims to test and analyze the effect of clarity of budget goals and accounting control on performance accountability in the Regional Secretariat of Lebak Regency. This research uses quantitative methods by collecting data using primary data. The population in this study was 91 respondents to setda employees. The sample in this study used a total sampling of only 63 respondents. This study used a likert scale. The analysis technique used in this study is multiple linear regression analysis. The result of this study is that clarity of budget goals on performance accountability has no effect. For the influence of accounting control on performance accountability has an effect. For clarity of budget goals and accounting control of performance accountability affects simultaneously in the Regional Regional Office of Lebak Regency..